Effect of vibro-milling time on phase formation and particle size of nickel niobate nanopowders - Khamman O. (2014)
A columbite-type phase of nickel niobate, NiNb2O6, nanopowder was synthesized by a solid-state reaction via a rapid vibro-milling technique. The effect of milling time on the phase formation and particle size of NiNb2O6 powder was investigated. Powder samples were characterized using DTA, XRD, SEM and laser diffraction techniques. It was found that the smallest particle size of 32 nm was achieved at 25 h of vibro-milling after which a higher degree of particle agglomeration was observed on continuation of milling to 35 h. In addition, by employing an appropriate choice of the milling time, a narrow particle size distribution curve was also observed. © 2008 Elsevier B.V. All rights reserved.